2021
DOI: 10.1021/acs.langmuir.1c00124
|View full text |Cite
|
Sign up to set email alerts
|

Fulvic Acid-Mediated Interfacial Reactions on Exposed Hematite Facets during Dissimilatory Iron Reduction

Abstract: Although the dual role of natural organic matter (NOM) as an electron shuttle and an electron donor for dissimilatory iron (Fe) reduction has been extensively investigated, the underlying interfacial interactions between various exposed facets and NOM are poorly understood. In this study, fulvic acid (FA), as typical NOM, was used and its effect on the dissimilatory reduction of hematite {001} and {100} by Shewanella putrefaciens CN-32 was investigated. FA accelerates the bioreduction rates of hematite {001} a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 75 publications
0
19
0
Order By: Relevance
“…For example, Gardea-Torresdey and coworkers have studied the impacts of metal oxide nanoparticles on plant health and nutritional value. Optimizing nanoparticles for adsorption , or dissolution , reactions requires knowledge of the interfacial chemistry at each face of the particle as well as control of the synthesis of nanoparticle habits during nucleation . Hence, improving our molecular-level information about complex nanoparticulate surface-solution chemistries will enable improving agricultural productivity by optimal time-release of nutrients and soil resilience by increasing retention of soil organic carbon.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Gardea-Torresdey and coworkers have studied the impacts of metal oxide nanoparticles on plant health and nutritional value. Optimizing nanoparticles for adsorption , or dissolution , reactions requires knowledge of the interfacial chemistry at each face of the particle as well as control of the synthesis of nanoparticle habits during nucleation . Hence, improving our molecular-level information about complex nanoparticulate surface-solution chemistries will enable improving agricultural productivity by optimal time-release of nutrients and soil resilience by increasing retention of soil organic carbon.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the spectra of dry goethite samples revealed how dehydration altered the molecular scale speciation of coexisting PA and silicate species. These observations are not only directly relevant to soils undergoing wet−dry cycling but also add further insight into the ever-growing literature 42,26,[43][44][45][46][47][48][49]27 on molecular-scale phenomena driving carboxylate-bearing organic ligand adsorption to mineral surfaces.…”
Section: Introductionmentioning
confidence: 59%
“…Of note, the relative importance of these species is affected by pH (MB at low and HB/OS at high pH), ionic strength (MB at high and HB/OS at low ionic strength), as well as the interplay of mineral surface and ligand structures. Fundamental surface science studies on low molecular weight carboxylic acids, which are the focus of this work, have been particularly beneficial along this front. …”
Section: Introductionmentioning
confidence: 99%
“…The physicochemical properties of metal sulfides, such as size, 28 surface defects, 29 and exposed facets, 30 are important factors affecting their surface reactions. Recent studies found that the facet-dependent interactions of biogenic or natural NPs, including dissolution, 29,30 crystallization, 31,32 redoxreaction, 33 fractionation, 34 and microbial transformation, 35 played an important role in various biogeochemical processes. In the anaerobic environment, microbes mediated the formation of CdS, and these CdS particles synthesized by different microorganisms consistently showed nano-size and spherical morphology.…”
Section: Environmental Significancementioning
confidence: 99%